IMAGEM INSTITUCIONAL: AVALIAÇÃO DA UNIVERSIDADE FEDERAL DA INTEGRAÇÃO LATINO-AMERICANA (UNILA) SEGUNDO O PÚBLICO INTERNO E EXTERNO - Fernanda Sotello (Revista Gestão Universitária na América Latina, 2018)
A growing number of studies have sought to evaluate the institutional image in different organizational segments. However, there are still few who associate the factors and attributes of Barich and Kotler's model (1991) as determinants in the image formation of universities. Based on the theoretical contribution of these authors, the objective of this study was to analyze the image of the Universidade Federal da Integração Latino-Americana - UNILA, second internal public (managers, technicians, teachers and students) and external (Foz do Iguaçu). The method with a descriptive and quantitative delineation was applied to 207 people from the internal public, and 269 from the external. As a result, it was found that the image of the university in factors such as Institutional Conduct; Social Behavior; Conduct with Servers; Support Activities; Infrastructure; Products and services; Price; And, Communication, is situated as regular (internally) and bad (externally). To improve that image, actions have been suggested as implementation of a communication committee and cascading information on the IES, monitoring of reports in the media about the UNILA, use of channels closer to the external community (newspapers, radio, social media, etc.), and periodic surveys to evaluate the image according to the internal and external public.